PEMBAYARAN ZAKAT PADA BADAN AMIL ZAKAT DAN LEMBAGA AMIL ZAKAT KAITANNYA DENGAN PAJAK PENGHASILAN - Tolkah, Tolkah (MAJALAH ILMIAH WIDYA, 2012)
Tax is one of revenue resources for the government treasury in almost parts of countries in the world. In Indonesia especiallytaxes aimed at supporting the purpose of national development. It is an obligation for all Indonesian citizens to pay taxes. Islam obligesMoslems to pay tithe. The Act No. 17 Year 2000 on the third revision of income tax, and it enables the tithe payment through AmilBoard of Tithe and Amil Agency of Tithe reducing income subjected to the tax. This research uses a juridical normative and descriptiveanalytic approach method, by using logical test and study on tithe, payment as a deducting device of income tax describes and analyzesthe available provisions related to tax and tithe. It can be concluded that: (1) In order to make the tithe reduce the income subjectedto tax, it should fulfill all the procedures that have been regulated. (2) To make the tithe more effective, executing regulation shouldbe formed by making good. Cooperation between the Finance Department and the Religion Department......................................